2013
DOI: 10.1179/1743281212y.0000000061
|View full text |Cite
|
Sign up to set email alerts
|

Influence of final stirring treatment on inclusion number in tool steel

Abstract: The focus was to study the elimination of non-metallic inclusions during the final part of the ladle refining of tool steel (AISI H13). More specifically, the final stirring treatment in a ladle before casting was modified to study how the number of inclusions could be decreased. The following three stirring treatments were tested: a conventional induction stirring with a 650 A current for 20 min, a short induction stirring with a 650 A current during 10 min, and a combined gas and induction stirring during 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 16 publications
2
10
0
Order By: Relevance
“…The present results with respect to sulfur and nitrogen refining agree with results from a previous study . Malmberg et al have reported that a degassing time of 15 min is sufficient with respect to sulfur and nitrogen refining.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The present results with respect to sulfur and nitrogen refining agree with results from a previous study . Malmberg et al have reported that a degassing time of 15 min is sufficient with respect to sulfur and nitrogen refining.…”
Section: Discussionsupporting
confidence: 92%
“…The aims of ladle treatment are many, namely refining with respective to sulfur, nitrogen and hydrogen, fine adjustment of the steel composition, homogenization as well as heating of the melt to reach optimum casting conditions, and inclusion removal. While a number of studies have been performed on the removal of hydrogen, nitrogen, and sulfur, many research works have been carried out to acquire a deeper understanding of the inclusion removal mechanisms during ladle refining …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Since then our group has carried out many studies focusing on determining how the inclusion characteristics vary during ladle treatment, based on plant trials [2][3][4][5][6]. Plant trials have also been made to study the following aspects of ladle refining operations: i) the effect of deoxidation praxis and ferroalloy additions on the inclusion characteristics [7][8][9], ii) the influence of the slag on the inclusion characteristics and sulphur content [10][11][12][13], iii) the influence of stirring on the inclusion characteristics [14][15][16][17] and the influence of sampling on determining the inclusion characteristics in process samples [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%